Some Methods of Solving Problems of Non-Linear Thermo-Viscoelasticity - Pobedria, B.E. (Engineering Transactions, 1974)
The formulation of the problems of non-linear thermo-viscoelasticity, including also coupled problems is given. For that purpose application of thermodynamics of irreversible processes to the visco-elastic media is analysed. Certain methods of subsequent approximations are presented for the solution of problems of non-linear theory of thermo-viscoelasticity, among other "rapidly convergent" method. The rate of convergence of these methods is analysed. Numerical methods are also considered, mainly the method of nets and the method of finite elements.